ANTIOXIDANT PROPERTIES of LENTINUS EDODES and AGARICUS BLAZEI EXTRACTS - Da Silva, Ana Carolina [UNESP]; Jorge, Neuza [UNESP] (Wiley-Blackwell, 2011)
This work aimed to evaluate the antioxidant activity of Lentinus edodes and Agaricus blazei mushrooms, as well as to measure the content of total phenolic compounds of mushroom extracts and verify the oxidative stability of soybean oil added with mushroom extracts that showed higher antioxidant activity according to the methods of the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and the beta-carotene/linoleic acid system. According to the DPPH method, the maximum antioxidant activity for L. edodes and A. blazei methanol extracts was 92.84 and 95.10%, respectively. For the beta-carotene/linoleic acid system, the highest values of antioxidant activity were 93.06% for L. edodes and 78.96% for A. blazei. The content of total phenolic compounds ranged from 7.21 to 128.44 and 26.67 to 134.67 mg gallic acid equivalent/g for L. edodes and A. blazei, respectively. The oxidative stability values provided by the Rancimat method indicated that the two varieties presented similar induction period of 19.85 h.